Challenges facing traditional ecological knowledge in the Vhembe District Municipality in Limpopo Province, South Africa - Ndidzulafhi Innocent Sinthumule (Social Sciences and Humanities Open)
Although TEK has been marginalised during colonial and apartheid era, over the past four decades, there has been a proliferation of research on TEK at local, regional and international levels. This is because, among other reasons, TEK provides multiple benefits to the bearers of such knowledge and contributes to the protection of the environment and ecosystem services. Despite this knowledge being important both for human and non-human environments, it faces several challenges among contemporary indigenous societies. Using the concept of power as a lens, this study aimed to investigate the challenges facing TEK using the Vhembe district in Limpopo Province (South Africa) as a case study. The study relied on semi-structured face-to-face interviews with local people. This method was found to be appropriate since it is flexible and allow for wide range of opinions that exceed the limits imposed by interview schedule. Key selected respondents included custodians of sacred sites, traditional leaders, bearers of TEK, educators, scholars dealing with TEK, curriculum experts, local pastors, and Christians. These respondents were selected using stratified purposeful sampling approach. A thematic content analysis was used to analyse the data obtained from the interviews. The study found that the cause of TEK system degradation is a complicated and multidisciplinary problem, including the compounding influences of dominant religions, formal education, new political dispensation, modernisation and advances in science and technology, as well as commercialisation. Recommendations for improving TEK management practices are drawn up based on these results.